Modulation of electronic and redox properties in phenolate-rich cobalt(iii) complexes and their implications for catalytic proton reduction1. Issue 7 (21st February 2015) - Basu, Debashis; Allard, Marco M.; Xavier, Fernando R.; Heeg, Mary Jane; Schlegel, H. Bernhard; Verani, Claudio N.
<x xml:space="preserve">Abstract</x> The redox, spectroscopic and catalytic activity of a series of cobalt complexes with phenolate-rich environments was investigated. The complex [CoIII(LCl)MeOH] shows considerable proton reduction in MeCN:HOAc with TON = 10.8.